FACTORS DETERMINING THE PURCHASE DECISION OF GREEN RESIDENTIAL PROPERTIES IN MALAYSIA - Chuweni, Nor Nazihah; Mohamed Saraf, Mohamad Haizam; Fauzi, Nurul Sahida; Che Kasim, Asmma’ (PLANNING MALAYSIA, 2022)
This study aims to determine and rank the factors influencing purchase decisions of green residential properties in Malaysia. The quantitative research approach was adopted in this study where the approach includes conducting surveys and analysing the quantitative data within green residential properties owners or residents with green certification mainly located in Penang and Selangor. Relative importance index is applied to data from a sample of 171 respondents through a purposive sampling. The main factors in influencing the green homebuyers’ decisions were found to be location factors followed by financial and neighbourhood and housing attributes. This study was the first to include green residential properties owners with green certification from Malaysian Green Building Index which focus only for green residential properties owners in Penang and Selangor as the sample of the study towards factors for influencing the purchase decision of green residential properties. Further development of empirical models could be developed and tested not only in other countries as well as to other types of green buildings. This study could provide best indicators for purchase decisions that could be embedded in the future green residential development. Stakeholders and policy makers could also provide incentive, recognition and take actions to increase awareness related to green development to internalise the medium-and long-term goals of green technology.